2001
DOI: 10.1023/a:1010325329898
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The purpose of this study was to determine how initial HIV prevention efforts for homeless youth were received and to determine areas where homeless youth's beliefs and behaviors continue to put them at risk for HIV infection. Interviews were conducted with 289 Seattle homeless youth. Youth reported using condoms with casual partners during vaginal and anal sex and with clients during oral, anal and vaginal sex. Condoms are often not used during vaginal sex with main partners or during oral sex with casual or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…[3][4][5] Additionally, the time spent on the street exposes them to drug users, sexual predators and other high-risk individuals who may exploit them and endanger their physical health. 6,7 Also, homeless youth have extremely low rates of condom usage and numerous sexual partners, 6,[8][9][10][11][12] which increases their risk for contracting STI. Self-reported rates of STI among homeless youth range from ~20% to 37%.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5] Additionally, the time spent on the street exposes them to drug users, sexual predators and other high-risk individuals who may exploit them and endanger their physical health. 6,7 Also, homeless youth have extremely low rates of condom usage and numerous sexual partners, 6,[8][9][10][11][12] which increases their risk for contracting STI. Self-reported rates of STI among homeless youth range from ~20% to 37%.…”
Section: Introductionmentioning
confidence: 99%
“…Self-reported rates of STI among homeless youth range from ~20% to 37%. 9,[12][13][14] It is estimated that 2.8 million runaway and homeless youth live on the streets of America every day 15 and because females and some minority groups, who are at greater risk for contracting STI, make up a sizeable portion of the homeless population, 16 homeless youth are an at-risk population in need of further study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One such challenge is pregnancy, as homeless youth pregnancy rates are as much as five times higher when compared to their housed counterparts Reeg, Grisham, & Shepard, 2002). National and regional studies report that 30% to 60% of female homeless youth indicate past or current pregnancies (Anderson, Freese, & Pennbridge, 1994;Cauce, Stewart, Whitbeck, Paradise, & Hoyt, 2005;Ensign, 2001;Halcón & Lifson, 2004;Haley, Roy, Leclerc, Boudreau, & Boivin, 2004;Milburn, Rotheram-Borus, Rice, Mallet, & Rosenthal, 2006;Wagner, Carlin, Cauce, & Tenner, 2001;Winetrobe et al, 2013), and at least 10% of female homeless youth are pregnant at any given time Herndon et al, 2003). Moreover, approximately 73% of pregnancies to homeless youth are unintended (Gelberg et al, 2001).…”
Section: Homeless Youth Pregnancymentioning
confidence: 99%
“…Regarding repeat pregnancies, 28% of a sample showed that homeless women had been pregnant two or more times (Halcón & Lifson, 2004), with another study illustrating that half of the homeless women in the sample reported four or more past pregnancies (Bassuk & Weinreb, 1993). Specifically among homeless youth, contraception and condom use is similarly met with ambivalence, inconsistency, and infrequency (Anderson et al, 1994;Haley et al, 2004;Solorio et al, 2008;Wagner et al, 2001). For instance, Anderson et al (1994) found that 30% of female and 40% of male street youth reported using condoms at last sexual intercourse, rates that were also further inconsistent in terms of usage with casual versus regular sexual partners.…”
Section: Homeless Youth Pregnancymentioning
confidence: 99%